THE JUSTIFICATION OF STATE INTERVENTION IN DISINCENTIVE TAXES UNDERTHE “LENS” OF PATERNALISM (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2025)
Tax law has long played an important role as a useful tool not only for obtaining funding resources for public affairs, but also for guiding taxpayers' behaviours on relevant issues, such as the protection of collective health. One of the classic examples is that of taxes on foods considered harmful to human health (the so-called junk food) and today used by many national systems to discourage their consumption. In these cases, it is necessary and useful to understand whether this attitude of the State, which can in practice represent a real interference in the individual sphere, can be framed within the scope of so-called paternalistic interventions, that is, in those acts of extreme politics which, while tending - with "paternal" solicitude - to the progress and well-being of the governed, does not consider them capable of pursuing such goals autonomously. This paper aims to analyse these tax strategies in consideration of the major theories on the subject, in order to understand whether they can be legally considered legitimate in the face of the autonomy and freedom of private individuals to engage in even "self-harming" behaviours (eating, for example, unhealthy food). From this perspective, the work also carries out an evaluation of the concept of health, trying to understand whether it can be qualified (as already happens for the environment) as a common good that everyone is required to protect without engaging in egoistic behaviours that, due to this collective dimension, can produce harmful effects for the entire community.Keywords: Eating habits, obesity, fiscal instruments, paternalism, health, common good